THE EFFECT OF BIBLIOCONSELING TECHNIQUES ON REDUCING BULLYING BEHAVIOR AT SMK NEGERI 5 BANTAENG - Syehrimuliani Masri; Abdullah Sinring; Farida Aryani (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to examine the effect of bibliocounseling techniques in reducing bullying behavior at SMK Negeri 5 Bantaeng. The study focuses on three main areas, namely the description of student bullying behavior, the description of the implementation of group counseling services using bibliocounseling techniques, and the effect of these techniques on reducing bullying behavior. The study uses a quantitative approach with a quasi-experimental design and a nonequivalent control group design. The research population consisted of all 22 students in class IX PMS, while the sample consisted of 12 students who were divided proportionally into an experimental group and a control group, each consisting of six students. The research instruments included a bullying behavior scale and observation guidelines. Data analysis was performed using descriptive statistics and parametric tests using the t-test. The results showed that the level of bullying behavior in the pretest stage in both groups was in the high category. After receiving treatment through bibliocounseling, the experimental group showed a significant decrease to the low category, while the control group remained in the high category. Bibliocounseling was carried out in five stages, namely preparation, reading literacy, self-exploration, providing in-depth insight, and follow-up. During the counseling process, student participation was excellent, and they began to realize the impact of their bullying behavior. Overall, the results of the study confirmed a significant difference between the experimental group and the control group. Thus, the bibliocounseling technique proved to be effective in reducing bullying behavior at SMK Negeri 5 Bantaeng.